PROSES IMPLEMENTASI KEBIJAKAN 5 (LIMA) HARI SEKOLAH DALAM PROSES BELAJAR MENGAJAR SISWA DAN GURU DI MADRASAH TSANAWIYAH NEGERI 2 POSO KABUPATEN POSO - Syuaib, Mohammad Rusli (Universitas Bina Taruna Gorontalo, 2025)
The purpose of this study is to find out the process of implementing the 5 (five) school days policy in the teaching and learning process of students and teachers at Madrasah Tsanawiyah Negeri 2 Poso, Poso Regency is measured by four existing indicators, namely the condition of the classroom environment, learning time, concentration and responsiveness which are indicators of Presidential Regulation No. 21 of 2023 concerning Working Days and Hours of Government Agencies and State Civil Apparatus. The method used is descriptive qualitative describing the problems that occur at the research location. The techniques used in data collection are observation, interviews and documentation. Data analysis using data reduction, data presentation, and conclusion drawing. The results of this study indicate that in the implementation of the 5 (five) school days policy, students and teachers feel uncomfortable being at school all day due to the density of learning time in the classroom. The factors that influence this study are individual circumstances and learning approaches.